PENENTUAN PRIORITAS PERBAIKAN JEMBATAN PADA JARINGAN JALAN PROVINSI JAWA TIMUR MENGGUNAKAN METODE INTEGRASI AHP-TOPSIS (Studi Kasus: Wilayah UPT. PJJ. Kediri) - Ni Putu Ayu Putri Kusuma Wardani; Raden Sulaiman (MATHunesa: Jurnal Ilmiah Matematika, 2023)
Infrastructure plays an important role in terms of supporting the country’s development because it supports the people’s mobility to get around, thereby pushing economic growth. Bridges are infrastructure capable of controlling traffic flow so bridge maintenance is important to the economy run well. The problem is the current condition, post-pandemic, there has been an increase in mobility in several public spaces, requiring adequate facilities and infrastructure. However, the addition of bridge infrastructure is currently not a top priority because there is a reduction in the amount of the budget. This study aims to determine the priority of bridge repair by weighting criteria using the AHP method and ranking priorities using the TOPSIS method. The criteria used in determining bridge repair priorities are the condition value of the bridge, the degree of saturation value and the condition value of strategic areas. In this study, the respondents were from 10 bridge experts. The results of the AHP analysis show that the value of the condition of the bridge has a weight of 0,572, the value of the degree of saturation has a weight of 0,146 and the value of strategic areas has a weight of 0,282. All of these weights will be used as input in the preference calculation using the TOPSIS method. Based on the calculation results of the TOPSIS method it was concluded that the Kalipucung II Bridge has the highest priority in terms of bridge repair with a preference value of 0,992 while the lowest priority belongs to Koang Baru with a preference value of 0,046. There are two bridges with the same ranking, namely Sukerejo I and II with a preference value of 0,518.